Mixed-litter effects of fresh leaf semi-decomposed litter and fine root on soil enzyme activity and microbial community in an evergreen broadleaf karst forest in southwest China - Mao, Bing; Cui, Tingting; Su, Tongqing; Xu, Qiangsheng; Lu, Feng; Su, Hongxin; Zhang, Jianbing; Xiao, Shuangshuang (Frontiers in Plant Science, 2022)
Litter decomposition is the main process that affects nutrient cycling and carbon budgets in mixed forests. However, knowledge of the response of the soil microbial processes to the mixed-litter decomposition of fresh leaf, semi-decomposed leaf and fine root is limited. Thus, a laboratory microcosm experiment was performed to explore the responses of soil enzyme activity and microbial community to litter mixing effects of fresh leaf, semi-decomposed leaf and fine root from Parakmeria nitida and Dayaoshania cotinifolia forests, which are unique protective species in an evergreen broadleaf forest in Southwest China. Our results showed that the mass loss of fresh leaf litter in three mixed-litter treatment was significantly higher than that in two mixed-litter treatment in P. nitida and D. cotinifolia forests. Mass loss of fine root in the single litter treatment was significantly lower in the P. nitida forest and higher in the D. cotinifolia forest than that in other litter treatments. There were insignificant differences in the activities of β-glucosidase and leucine aminopeptidase between control and mixed-litter treatment in the P. nitida forest and between control and single litter treatment in the D. cotinifolia forest. The N-acetyl-β-D-glucosaminidase activity was significantly increased by the single litter of fresh leaf and fine root and three mixed-litter in P. nitida and D. cotinifolia forests. The activity of acid phospomonoesterase in the decomposition of fresh leaf litter was lower in the P. nitida forest and higher in the D. cotinifolia forest compared to that in control. Shannon, Chao1, ACE and PD indexes in mixed-litter decomposition of fresh leaf and semi-decomposition litter were higher than that in control in P. nitida forest. There were insignificant differences in Chao1, ACE and PD indexes between litter treatments in the D. cotinifolia forest. Litter N concentration and the presence of fresh leaf litter were significantly correlated with the mass loss and soil enzyme activity in P. nitida and D. cotinifolia forests. These results indicated that the presence of fresh leaf litter showed a non-negligible influence on mixed-litter decomposition and soil enzyme activity, which might be explained by litter initial quality in P. nitida and D. cotinifolia forests.